Pranayama Yoga and Music Therapy: A Holistic Rehabilitation Therapy Combination for Chronic Obstructive Pulmonary Disease Patient (Jurnal Ilmu Kesehatan Masyarakat, 2020)
The management of certain health disorder can be done through a combination of conventional methods, namely with medicine, as well as traditional in a holistic (comprehensive) manner. The same also can be done for people with chronic obstructive pulmonary disease (COPD). Breath training technique and self-relaxation can be used as a complement, in addition to the consumption of drugs. Yoga pranayama combined with music therapy is a new rehabilitation therapy combination that can be implemented. This study was a narrative literature review composed by original articles and reviews written in English, aims to determine the potential of a combination of yoga pranayama and music therapy as a holistic rehabilitation therapy in patients with COPD. That therapy combination has been proven capable by some literatures in reducing dyspnea, increasing lung capacity and oxygen saturation, improving fitness and minimizing anxiety level, however, there were not any studies that ensure the potency of this therapy combination in COPD patients, therefore further research should be addressed.